Isoflurane : interaction with hepatic microsomal enzymes - Bradshaw, Jennifer Jean (Division of Medical Biochemistry and Structural Biology, 2018)
lsoflurane interacts with cytochrome P-450 in rat and human hepatic microsomes and the Δ6- and Δ5-desaturases in rat hepatic microsomes. The interaction of isoflurane with cytochrome P-450 results in its metabolism to fluoride ion and organofluorine metabolites. The cytochrome P-450 isozymes catalysing the defluorination of isoflurane were assessed in hepatic microsomes from phenobarbital-, β-naphthoflavone- and pregnenolone-16α-carbonitrilepretreated and untreated rats. One or more of the cytochrome P-450 isozymes induced by phenobarbital and pregnenolone-16α-carbonitrile appear to defluorinate isoflurane, but those induced by β-naphthoflavone do not. From a comparison of the extent of defluorination of isoflurane in hepatic microsomes from phenobarbital- and pregnenolone-16α-carbonitrile-pretreated rats, and their Kₘ and Vₘₐₓ values, it appears that isoflurane is defluorinated by one or more isozymes induced by both phenobarbital and pregnenolone-16α-carbonitrile. The major isozyme is probably cytochrome P-450PCN1. The metabolites of isoflurane were identified in human and phenobarbital-induced rat hepatic microsomes. In microsomes from phenobarbital-pretreated rats, isoflurane is metabolised to fluoride ion and trifluoroacetaldehyde; trifluoroacetic acid is not produced in measureable amounts. The trifluoroacetaldehyde produced binds to microsomal constituents. In human hepatic microsomes, the organofluorine metabolite is identified as trifluoroacetic acid. It is proposed that isoflurane is metabolised by different pathways in human and phenobarbital-induced rat hepatic microsomes. The interaction of isoflurane with the cyanide-sensitive factors was assessed by several criteria. Firstly, using the reoxidation of cytochrome b₅ as an index of fatty acid desaturase activity, isoflurane appears to interact with the Δ6- and/or Δ5-desaturases, but not the Δ9-desaturase. Secondly, these results were confirmed and clarified by the use of direct assays to measure the fatty acid desaturase activity. Using the direct assay, we confirmed that isoflurane did not inhibit the Δ9-desaturase and inhibited Δ6-desaturation of linoleic acid, but not the Δ6-desaturation of α-linolenic acid. The inhibition of the Δ6-desaturation of linoleic acid occurred at low millimolar concentrations of isoflurane. lsoflurane inhibits the Δ5-desaturation of eicosa-8, 11, 14-trienoic acid to a small extent which is only apparent at much higher concentrations of isoflurane than that which inhibits the Δ6-desaturase. Further studies focussed on measurement of the activity of Δ6-desaturase in order to attempt to study the kinetics of the inhibition of the Δ6-desaturase by isoflurane: Δ6-desaturase activity was assessed using hepatic microsomes as the source of the enzyme and linoleic acid as substrate precursor. In the course of these studies, we identified a number of factors that affected the apparent activity of the Δ6-desaturase in hepatic microsomes. These included significant levels of endogenous substrate and competing reactions in the hepatic microsomes. Endogenous substrate levels were quantified and corrected for. We then resorted to computer modelling to extract the kinetics of the Δ6-desaturase free of contributions from acyl-CoA synthetase and lysophospholipid acyltransferase, as well as enzyme decay. The kinetics of isoflurane inhibition of the Δ6-desaturase were then superimposed and studied by computer modelling.